The Universe - Bergamini, David; Editors of TIME-LIFE BOOKS (Time-Life Books : Hong Kong, 1980)
A richly illustrated, juvenile-level astronomy book covering: Myths and misconceptions Solar system, stars, galaxies, cosmology Space exploration and human ventures beyond Earth Designed for general readers/students, offering clear text, color photos, diagrams, and maps.
Keywords: Astronomy